PEMANFAATAN BATU PADAS DALAM MENGADSORPSI LOGAM BERAT Pb (II) DI PERAIRAN - Hutapea, Tri Paus Hasiholan; Yusuf, Bohari; Purba, Ritson (Jurnal Harpodon Borneo, 2016)
The research of increasing adsorption of the heavy metal iron by padas stone that activated by NaOH 4 N. The Result of survey show that acidity surface and capacity adsorption of padas stone that activited by a NaOH 4 N higher than padas stone which unactivited. Which acidity of surface and higher adsorption capacity aconed by padas stone that activited by NaOH 4 N namely 0,100 mmol/gram. In this research has show the increasing of padas stone adsorption to the ion heavy iron metal. Kata kunci : stone of padas ; adsorption ; Heavy metal ; Pb (II)